Approaches to Governance in Fragile and Conflict Situations : A Synthesis of Lessons - Messineo, Carol; Wam, Per Egil (World Bank, Washington, DC, 2017)
Developing a diagnostic and action framework for donor-assisted governance reform in conflict-affected countries and fragile states was the objective of a program implemented by the World Bank's Social Development Department (SDV) and funded by the French Ministry of Foreign Affairs. The first phase of the program developed lessons and outcomes based upon a review of international experience of governance reform in fragile and conflict-affected states. A major objective was to identify specific approaches and activities that will be most effective in strengthening institutions, promoting transparency and accountability, and enhancing capacity at local and national levels. This phase also derived lessons on the utility and shortcomings of governance-related diagnostic tools in designing and evaluating country strategies and programs in fragile states. A key issue concerns methodology. What type of analytical method provides a more useful assessment: country-specific analyses of the political economy, indicators designed for purposes of cross-country comparison, indices that rank state fragility, or some combination of diagnostic tools? The second phase of the program also was in two parts. Cote d'Ivoire's poverty reduction strategy process was used as an entry point for an initiative that facilitated process and method-oriented exercises for local stakeholders on the how rather than the what of policy development in an effort to build governance capacity. One result is a model that may serve for future engagement in other fragile and conflict-affected countries. The second part of this phase is an ongoing effort to work with local partners in the Central African Republic and Chad to identify strategies that could strengthen access to justice at the local level. Activities include assessing the strengths and weaknesses of formal and informal justice systems and mapping community-based practices and informal justice systems, including some under the aegis of NGOs, as well as identifying possible linkages to state justice systems. The paper will first examine the concepts of state fragility and governance in terms of donor engagement. Part two will discuss the lessons (opportunities and constraints), diagnostic tools and entry points for governance reform. Part three will offer conclusions.